Faktor-faktor yang Mempengaruhi Investasi Asing Langsung di Indonesia - Azizan, Muhammad; Barany, Ernawati; Simbolon, Polma Risma; Novianti, Tanti (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2025)
Foreign Direct Investment (FDI) plays a pivotal role in Indonesia’s economic growth. However, its realization is significantly influenced by various economic factors, particularly macroeconomic stability. This study aims to analyze the impact of foreign direct investment (FDI) in the previous period, inflation, gross domestic product (GDP) in the previous period, and the economic crisis dummy on foreign direct investment (FDI) in Indonesia. The study utilizes annual time series data covering the period from 1995 to 2023. A quantitative approach is employed, applying a multiple regression model analyzed using the Ordinary Least Squares (OLS) method. The findings indicate that, simultaneously, foreign direct investment (FDI) in the previous period, inflation, gross domestic product (GDP) in the previous period, and the economic crisis dummy significantly influence foreign direct investment (FDI) in Indonesia. Partially, foreign direct investment (FDI) in the previous period has a significant and positive effect, inflation has a significant and negative effect, and gross domestic product (GDP) in the previous period has a significant and positive effect. Meanwhile, the economic crisis dummy does not have any significant impact on the constructed model.